Communities of discourse : ideology and social structure in the Reformation, the Enlightenment, and European socialism - Wuthnow, Robert (Harvard University Press, 1989)
Sociologist Robert Wuthnow notes remarkable similarities in the social conditions surrounding three of the greatest challenges to the status quo in the development of modern society--the Protestant Reformation, the Enlightenment, and the rise of Marxist socialism.